Alkane normal isomerization catalyst as well as preparation method and application thereof
By introducing all-silicon molecular sieve and alumina with MFI structure in the catalyst, the acid center distribution is modified, and the problems of insufficient catalytic activity and difficult to take into account both the conversion and selectivity in the prior art are solved, and normal alkanes are achieved Higher activity and selectivity in the strulation reaction.
Patent Information
- Application Number
- CN202311049651.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
The prior art lacks a bifunctional catalyst of positive isomerization, which has insufficient catalytic activity and is difficult to take into account both conversion and selectivity.
Provided is an alkane isomerization catalyst including acid active component SO42-/ZrO2, a full silicon molecular sieve with an MFI structure, and an alumina monoisomerization catalyst. By adjusting the acid center distribution of the catalyst, the catalyst can be improved in the normal isomerization reaction. Activity and selectivity.
In the norm isomerization reaction of light alkanes, the catalyst exhibits good catalytic activity and selectivity, taking into account both conversion and selectivity.
Smart Images

Figure CN119488938A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of normal isomerization of light alkanes, and in particular to a normal isomerization catalyst for alkanes, a preparation method thereof and an application thereof. Background Art
[0002] The normal isomerization of light alkanes mainly includes C5 / C6 isomerization, n-butane isomerization and isobutane normalization. Among them, C5 / C6 isomerization is used to produce C5 / C6 isomerized oil, which basically does not contain sulfur, olefins and aromatics, and is an important clean gasoline blending component. N-butane isomerization can convert n-butane into isobutane, providing isobutane raw materials for butane-butene alkylation, isobutane-propylene co-oxidation (PO / MTBE), C3 / iC4 alkane dehydrogenation, isobutane dehydrogenation and other processes. Therefore, the normal isomerization of light alkanes is an important supporting technology for upgrading the quality of oil products, an important means to expand the raw material source of ethylene units, and a key unit technology for processes such as n-butane oxidation to produce maleic anhydride, C3 / C4 alkane dehydrogenation, isobutane dehydrogenation, and PO / MTBE.
[0003] Solid superacid catalyst is a new type of catalyst developed in recent years, among which inorganic acid-promoted zirconium-based solid superacid catalyst has shown good performance in light hydrocarbon isomerization reaction. CN1164509A discloses a molecular sieve type superacid and its preparation method, wherein the catalyst is hydrogen-type ZSM-5, ZSM-11 or β molecular sieve containing Ti or Zr metal elements. When the catalyst of the invention is used for n-butane isomerization reaction, at 100°C, normal pressure, and n-butane gas space velocity of 800h -1 Under the condition of , the conversion rate of n-butane is 35% and the selectivity of isobutane is 78%. CN101745407A discloses a solid superacid catalyst and its preparation method. The catalyst converts zirconium hydroxide into a catalyst containing SO4 2- The catalyst is prepared by impregnating the catalyst with a solution of , drying it, mixing it with silica sol, extruding it into a mold, calcining it, and then impregnating it with a Group VIII metal. CN110385142A discloses a catalyst for isobutane normalization reaction, which uses MCM-41 molecular sieve as a carrier and Pt / SO4 2- / ZrO2 is the active component. Although the reaction conditions are relatively mild, the isobutane conversion effect is not ideal. Under the condition that the n-butane selectivity is higher than 90%, the isobutane conversion rate does not exceed 21%, and the n-butane yield is lower than 22.1%.
[0004] The sulfated zirconium oxide type solid superacid catalyst disclosed in the prior art is usually used for isomerization or normalization, and there is no report on its application in both reactions. In addition, when the catalyst disclosed in the prior art is used for isomerization or normalization reaction, there is still a problem that it is difficult to balance the reaction conversion rate and target product selectivity. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems in the prior art of lack of a bifunctional catalyst for normal isomerization, insufficient normal isomerization activity, and difficulty in balancing conversion rate and selectivity, and to provide an alkane normal isomerization catalyst and a preparation method and application thereof. The catalyst exhibits good catalytic activity and selectivity in the normal isomerization reaction of light hydrocarbons.
[0006] In order to achieve the above object, the present invention provides a catalyst for the normal isomerization of alkanes, the catalyst comprising an acidic active component SO4 2- / ZrO2, all-silicon molecular sieve with MFI structure and alumina;
[0007] The mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.1-1).
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned alkane normal isomerization catalyst, the preparation method comprising:
[0009] (1) mixing an all-silicon molecular sieve having an MFI structure and zirconium hydroxide to obtain a mixture;
[0010] Wherein, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.1-1);
[0011] (2) contacting the mixture with a solution containing sulfate;
[0012] (3) The product obtained in step (2), an alumina precursor and an optional peptizing agent are mixed, and then molded and calcined.
[0013] The third aspect of the present invention provides use of the above-mentioned alkane normal isomerization catalyst in the normal isomerization reaction of light alkanes.
[0014] The catalyst provided by the present invention comprises an acidic active component SO4 2- / ZrO2, all-silicon molecular sieve with MFI structure and alumina. The acid center of the catalyst is modulated by all-silicon molecular sieve with MFI structure. Under the condition of not changing the active phase structure and acid strength of the catalyst, the distribution of the acid center of the catalyst is optimized, the proportion of unimolecular reaction in the normal isomerization reaction is increased, and the proportion of bimolecular reaction is reduced, so that the catalyst shows good activity and selectivity in the normal isomerization reaction of light alkanes. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1It is the XRD spectra of the all-silicon MFI molecular sieve, white carbon black, MCM-41 molecular sieve and ZSM-5 molecular sieve used in the examples and comparative examples of the present invention;
[0016] Figure 2 It is the XRD spectra of the catalysts prepared in Examples 1-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides a catalyst for the normal isomerization of alkanes, the catalyst comprising an acidic active component SO4 2- / ZrO2, all-silicon molecular sieve with MFI structure and alumina;
[0019] The mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.1-1).
[0020] The phase analysis of the catalyst samples was carried out using a Japanese Rigaku D / MAX-3A diffractometer (XRD) under the following analysis conditions: radiation source CuKα target, Ni filter, scanning range 5°-70°, step width 0.02°.
[0021] In the solid acid catalyst system in the prior art, molecular sieves are usually used as carriers, and the molecular sieves used as carriers occupy a relatively high content in the catalyst; at the same time, the silicon-aluminum molecular sieve introduced into the catalyst is also usually used to provide additional acidic active centers.
[0022] The inventors of the present invention have found in their research that a small amount of all-silicon molecular sieves and alumina with an MFI structure can play a role in adjusting the distribution of strong acid centers of solid acid catalysts, so that the catalyst exhibits high activity and high selectivity in the normal isomerization reaction. The reason for this is that, on the one hand, the all-silicon molecular sieve with an MFI structure has basically no acidity and excellent thermal stability, which can avoid the introduction of new acid centers and optimize the distribution of strong acid centers in zirconium sulfate oxide, which is conducive to the efficient activation and conversion of alkane molecules through a single molecule path. On the other hand, the special pore structure of the all-silicon molecular sieve with an MFI structure is conducive to the diffusion of reactants and products, thereby effectively avoiding the occurrence of secondary reactions.
[0023] According to some preferred embodiments of the present invention, in the catalyst, the mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.15-0.5), for example, it can be typical but non-limiting mass ratios such as 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, etc.
[0024] According to some preferred embodiments of the present invention, the catalyst comprises zirconium, silicon, aluminum and sulfur, and the content of zirconium oxide, silicon oxide, aluminum oxide and SO3 is respectively calculated based on the total mass of the catalyst, and the content of zirconium oxide is 30-90wt%, the content of silicon oxide is 1-35wt%, the content of aluminum oxide is 5-50wt%, and the content of SO3 is 1-10wt%; preferably, based on the total mass of the catalyst, the content of zirconium oxide is 50-80wt%, the content of silicon oxide is 5-30wt%, the content of aluminum oxide is 5-30wt%, and the content of SO3 is 2-8wt%. Under the above preferred composition, it is beneficial to improve the thermal stability of tetragonal zirconium oxide and the specific surface area of the catalyst, so that the catalyst has a suitable distribution of strong acid centers and accessibility of active centers, and the catalytic activity of the catalyst is further improved.
[0025] Preferably, the mass ratio of SO3 to ZrO2 is (0.02-0.12):1, preferably (0.03-0.08):1.
[0026] In the present invention, the catalyst composition is characterized and analyzed using an XRF-1800 wavelength dispersive X-ray fluorescence spectrometer, and the content of each element in the sample is obtained through theoretical calculation and mathematical correction based on the intensity of the elements present in the sample obtained by scanning and the pure substance sensitivity of these elements in the instrument.
[0027] In the present invention, the catalyst specific surface area is characterized by low-temperature nitrogen static volume adsorption method (BET method). The instrument used is ASAP2400 specific surface measuring instrument produced by Micromeritics Instruments. The pretreatment conditions are: 250°C, 1.3Pa, treatment for 4h, and the specific surface area is calculated using the BET formula.
[0028] In the present invention, the density of the strong acid center is the ratio of the amount of strong acid in the catalyst to the specific surface area. The method for testing the amount of strong acid in the catalyst includes: using a Nicolet 6700 Fourier transform infrared spectrometer produced by Thermo Fisher, USA, with a resolution of 4 cm -1, scanned 64 times. The sample was pressed into a self-supporting sheet with a diameter of 13 mm, and then placed in a muffle furnace for high-temperature calcination. After completion, it was directly transferred to a dryer for cooling at high temperature. After cooling to room temperature, it was placed in a homemade quartz infrared sample cell, first treated at 400°C for 2 hours under normal pressure flowing air, then cooled to 200°C, vacuum purified for 4 hours, and then cooled to -190°C with liquid nitrogen. The purified CO probe molecules were saturated and adsorbed for 0.5 hours before desorption. The spectra before and after adsorption were subtracted to obtain the infrared spectrum of the sample adsorbed CO. For the wave number of 2050-2250cm -1 The spectrum at 2186cm is processed by peak separation. The spectrum can be divided into four absorption peaks with wave numbers of 2186cm -1 、2167cm -1 、2150cm -1 and 2125cm -1 , where the wave number is 2167cm -1 The absorption peak at is the strong acid center which is directly related to the catalyst performance. The strong acid amount N (in μmol / g) is calculated according to formula (1).
[0029] N=A / (ρA0), formula (1),
[0030] Where A is the integrated area of the absorption peak (in cm -1 ), ρ is the mass of the catalyst support per square centimeter (in g / cm 2 ), A0 is the molar extinction coefficient, for a wave number of 2167 cm -1 The spectral peak is A0=2.6cm / μmol.
[0031] The catalyst provided by the present invention has a suitable density of strong acid centers, while the density of strong acid centers in the super strong solid acid sulfate zirconium oxide in the prior art is relatively high, generally higher than 2 μmol / m 2 The inventors of the present invention have found in their research that too high a density of strong acid centers may affect the selectivity of the normal isomerization catalyst.
[0032] The inventors of the present invention have found in their research that the presence of strong acid sites with suitable density and uniform strength in the catalyst is conducive to the efficient activation and conversion of the reactant molecules through a single molecule pathway, thereby enabling the catalyst to exhibit both high activity and high selectivity in the normal isomerization reaction.
[0033] According to some preferred embodiments of the present invention, the density of the strong acid center in the catalyst is 0.1-2 μmol / m 2 , preferably 0.5-1.5 μmol / m 2 , for example, 0.5 μmol / m 2 , 0.6μmol / m 2 , 0.7 μmol / m2 , 0.8 μmol / m 2 , 0.9 μmol / m 2 , 1μmol / m 2 , 1.1 μmol / m 2 , 1.2 μmol / m 2 , 1.3 μmol / m 2 , 1.4 μmol / m 2 , 1.5 μmol / m 2 The above preferred conditions are beneficial to further improve the activity and selectivity of the catalyst in the normal isomerization reaction.
[0034] According to some preferred embodiments of the present invention, the specific surface area of the catalyst is 80-180 m 2 / g, preferably 90-160m 2 / g, more preferably 100-150m 2 / g.
[0035] According to some preferred embodiments of the present invention, the aluminum oxide is γ-Al2O3. In the above preferred case, it is beneficial to improve the thermal stability and specific surface area of the catalyst, thereby improving the catalytic activity of the catalyst.
[0036] In the present invention, there is no particular limitation on the shape of the catalyst, and those skilled in the art can select it according to actual needs. For example, it can be in the form of strips, pellets, sheets, particles or microspheres, suitable for fixed bed, moving bed or fluidized bed reactions.
[0037] The second aspect of the present invention provides a method for preparing the above-mentioned alkane normal isomerization catalyst, the preparation method comprising:
[0038] (1) mixing an all-silicon molecular sieve having an MFI structure and zirconium hydroxide to obtain a mixture;
[0039] Wherein, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.1-1);
[0040] (2) contacting the mixture with a solution containing sulfate;
[0041] (3) The product obtained in step (2), an alumina precursor and an optional peptizing agent are mixed, and then molded and calcined.
[0042] According to the present invention, the above-mentioned preparation method can make the all-silicon molecular sieve with MFI structure evenly distributed in the catalyst without blocking the catalyst pores, and the density of the strong acid center in the sulfated zirconium oxide is reduced without introducing new acid centers. The presence of strong acid sites with suitable density and uniform strength is conducive to the efficient activation and conversion of reactant molecules through a single molecule path, so that the catalyst exhibits high activity and high selectivity in the normal isomerization reaction.
[0043] The present invention has a wide selection range for the number of pores and the pore structure of the all-silicon molecular sieve, and any all-silicon molecular sieve with an MFI structure can be applied to the present invention.
[0044] In some preferred embodiments, the specific surface area of the all-silicon molecular sieve is 400-500m 2 / g, preferably 420-460m 2 In the above preferred case, it is beneficial to further optimize the density of the strong acid center in the sulfated zirconium oxide, improve the uniformity of the strong acid site, and thus improve the normal isomerization activity.
[0045] According to some preferred embodiments of the present invention, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.15-0.5).
[0046] In the present invention, the acidic active component is formed by contacting the mixture with a solution containing sulfate in step (2). The contact can be carried out in a conventional manner in the art, for example, the mixture can be impregnated with a solution containing sulfate.
[0047] The present invention has no particular limitation on the specific operating conditions of the contact, as long as the catalyst composition range described above is met, and those skilled in the art can make the selection according to actual needs.
[0048] According to some preferred embodiments of the present invention, the contacting temperature is 20-80°C, preferably 25-60°C; and the contacting time is 1-10h, preferably 2-5h.
[0049] The present invention has a wide range of selection for the specific type of the solution containing sulfate radicals. Preferably, the solution containing sulfate radicals is selected from an aqueous solution of at least one of sulfuric acid, ammonium sulfate and ammonium bisulfate.
[0050] Preferably, the concentration of sulfate in the solution containing sulfate is 1-10wt%, preferably 2-8wt%. The above preferred embodiment is conducive to obtaining a suitable SO3 content and strong acid center density.
[0051] The present invention has no particular limitation on the amount of the solution containing sulfate, as long as it meets the requirements of the SO3 content range in the catalyst described in the first aspect, and those skilled in the art can select it according to actual needs. Preferably, the mass ratio of the solution containing sulfate to the mixture is 0.3-5:1, preferably 0.5-3:1.
[0052] In the present invention, after the contacting in step (2), an optional drying and grinding step is further included. The drying temperature may be 50-150° C., and the drying time may be 3-100 hours. The grinding is used to grind the dried solid into a powder of 100-300 meshes, which is beneficial to improve the crushing strength of the catalyst in the above preferred case.
[0053] In the present invention, the alumina precursor refers to a substance that can obtain alumina by calcination, which is well known to those skilled in the art. Preferably, the alumina precursor is pseudo-boehmite and / or gibbsite, preferably pseudo-boehmite. The above preferred alumina precursor can be calcined to form γ-Al2O3, which is beneficial to improve the thermal stability and crushing strength of the catalyst.
[0054] In the present invention, the molding in step (3) can be carried out by conventional methods and conditions in the art, and the present invention has no particular limitation thereto. The molding method can be selected according to the actual application needs, for example, it can be selected from any one of extrusion molding, granulation molding, ball rolling molding and spray drying spheronization, preferably extrusion molding. In the above preferred case, it is more suitable for a fixed bed reactor.
[0055] According to some preferred embodiments of the present invention, the total mass ratio of the peptizing agent to the product obtained in step (2) to the alumina precursor is 0.3-1:1, preferably 0.4-0.8:1.
[0056] According to some preferred embodiments of the present invention, the peptizing agent is an aqueous solution of an acid, preferably an aqueous solution of at least one selected from nitric acid, acetic acid, citric acid, oxalic acid and formic acid.
[0057] Preferably, the concentration of the acid in the peptizing agent is 2-10 wt %.
[0058] According to some preferred embodiments of the present invention, in step (3), the calcination temperature is 600-850° C., preferably 650-850° C., and the calcination time is 1-20 hours, preferably 3-12 hours. Under the above preferred calcination temperature conditions, it is beneficial to form a strong acid center with a suitable density, which is beneficial to improve the activity and selectivity of the catalyst in the butane isomerization reaction.
[0059] In the present invention, step (3) may further include a drying process before the calcination. Preferably, the drying temperature is 80-140° C., preferably 100-130° C., and the drying time is 5-30 hours, preferably 8-24 hours.
[0060] The third aspect of the present invention provides use of the above-mentioned alkane normal isomerization catalyst in the normal isomerization reaction of light alkanes.
[0061] Preferably, the light alkane normal isomerization reaction includes C5 / C6 isomerization, normal butane isomerization and isobutane normalization reactions.
[0062] Preferably, the light alkane normal isomerization reaction is carried out in a fixed bed reactor.
[0063] The present invention will be described in detail below through examples.
[0064] The bulk structure of the molecular sieve and the catalyst was analyzed and detected by using a Japanese Rigaku D / MAX-3A diffractometer (XRD). The analysis conditions were: radiation source CuKα target, Ni filter, scanning range 5°-70°, step width 0.02°.
[0065] The composition of molecular sieve and catalyst was characterized and analyzed by XRF-1800 wavelength dispersive X-ray fluorescence spectrometer. The content of each element in the sample was obtained through theoretical calculation and mathematical correction based on the intensity of the elements present in the sample obtained by scanning and the sensitivity of the pure substances of these elements in the instrument.
[0066] The zirconium hydroxide powder used was purchased from Changling Catalyst Company, and the zirconium oxide content was 78.5% by weight.
[0067] The all-silicon MFI molecular sieve Si-1 used was purchased from Changling Catalyst Company, with a silicon oxide content of 99.7% by mass and a specific surface area of 444.6 m 2 / g, XRD characterization Figure 1 shown.
[0068] Pseudo-boehmite powder was purchased from Sasol, Germany, with an alumina content of 75% by mass.
[0069] Example 1
[0070] Take 38.2g of zirconium hydroxide powder and 4.4g of all-silicon MFI molecular sieve Si-1 and mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, soak at 40°C for 4h, and dry the impregnated solid at 60°C for 12h and 120°C for 12h.
[0071] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, and mixed evenly with 14.4 g of pseudo-boehmite powder. A nitric acid aqueous solution with a concentration of 5.0 mass % was added for peptization. The ratio of the total mass of the nitric acid aqueous solution to the fine powder and the alumina precursor was 0.6:1. After kneading evenly, the wet strips were extruded into strips. The wet strips were dried at 120°C for 10 hours and calcined at 680°C for 4 hours to obtain catalyst A1. The XRD characterization results of catalyst A1 are shown in Figure 2 ,Depend on Figure 2 The characteristic peaks of all-silicon MFI molecular sieve can be seen; the composition and physicochemical properties of the catalyst are shown in Table 1 and Table 1.
[0072] Example 2
[0073] Take 38.2g of zirconium hydroxide powder and 7.8g of all-silicon MFI molecular sieve, mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, soak at 40°C for 4h, and dry the soaked solid at 60°C for 12h and 120°C for 12h.
[0074] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, and mixed evenly with 10.6 g of pseudo-boehmite powder. A nitric acid aqueous solution with a concentration of 5.0 mass % was added for peptization. The ratio of the total mass of the nitric acid aqueous solution to the fine powder and the alumina precursor was 0.5:1. After kneading evenly, the wet strips were extruded into strips. The wet strips were dried at 120°C for 10 hours and calcined at 680°C for 4 hours to obtain catalyst A2. The XRD characterization results of catalyst A2 are shown in Figure 2 The composition and physicochemical properties are shown in Table 1 and Table 1.
[0075] Example 3
[0076] Take 38.2g of zirconium hydroxide powder and 14.3g of all-silicon MFI molecular sieve, mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, soak at 40°C for 4h, and dry the soaked solid at 60°C for 12h and 120°C for 12h.
[0077] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, and mixed evenly with 3.4 g of pseudo-boehmite powder. A nitric acid aqueous solution with a concentration of 5.0 mass % was added for peptization. The ratio of the total mass of the nitric acid aqueous solution to the fine powder and the alumina precursor was 0.7:1. After kneading evenly, the wet strips were extruded into strips. The wet strips were dried at 120°C for 10 hours and calcined at 680°C for 4 hours to obtain catalyst A3. The XRD characterization results of catalyst A3 are shown in Figure 2 The composition and physicochemical properties are shown in Table 1 and Table 1.
[0078] Example 4
[0079] The method of Example 2 was followed, except that the amount of all-silicon MFI molecular sieve Si-1 used was 21 g. The prepared catalyst was denoted as A4, and the composition and physicochemical properties are shown in Table 1 and Table 1.
[0080] Example 5
[0081] 38.2 g of zirconium hydroxide powder was taken, 48.0 g of a 5 mass % sulfuric acid aqueous solution was added, and the mixture was immersed at 40° C. for 4 h. The immersed solid was dried at 60° C. for 12 h and 120° C. for 12 h.
[0082] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, 7.8 g of all-silicon MFI molecular sieve and 10.6 g of pseudo-boehmite powder were added thereto, mixed evenly, and 5.0 mass % nitric acid aqueous solution was added for peptization, the ratio of the total mass of the nitric acid aqueous solution to the fine powder and the alumina precursor was 0.6:1, and after kneading evenly, the strips were extruded, and the wet strips were dried at 120°C for 10 hours and calcined at 680°C for 4 hours to obtain catalyst A5. The composition and physicochemical properties of A5 are shown in Table 1 and Table 1.
[0083] Example 6
[0084] Take 38.2g of zirconium hydroxide powder and 6.0g of all-silicon MFI molecular sieve Si-1, mix them evenly, add 48.0g of 3% by mass sulfuric acid aqueous solution, soak at 40°C for 4h, and dry the impregnated solid at 60°C for 12h and 120°C for 12h.
[0085] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, and mixed evenly with 38.3 g of pseudo-boehmite powder, and peptized by adding a nitric acid aqueous solution with a concentration of 5.0 mass %, the ratio of the nitric acid aqueous solution to the total mass of the fine powder and the alumina precursor being 0.6:1, and after kneading evenly, extruded into strips, and the wet strips were dried at 120° C. for 10 h and calcined at 630° C. for 4 h to obtain catalyst A6. The composition and physicochemical properties of catalyst A6 are shown in Table 1 and Table 1.
[0086] Comparative Example 1
[0087] 38.2 g of zirconium hydroxide powder was taken, 48.0 g of a 5 mass % sulfuric acid aqueous solution was added, and the mixture was immersed at 40° C. for 4 h. The immersed solid was dried at 60° C. for 12 h and 120° C. for 12 h.
[0088] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, and mixed evenly with 16.6 g of pseudo-boehmite powder. A nitric acid aqueous solution with a concentration of 5.0 mass % was added for peptization. The ratio of the total mass of the nitric acid aqueous solution to the fine powder and the alumina precursor was 0.6:1. After kneading evenly, the wet strips were extruded into strips. The wet strips were dried at 120°C for 10 hours and calcined at 680°C for 4 hours to obtain catalyst DA1. The XRD characterization results of catalyst DA1 are shown in Figure 2 It can be seen that the catalyst DA1 does not contain the characteristic peak of the all-silicon MFI molecular sieve Si-1. The composition and physicochemical properties of the catalyst DA1 are shown in Table 1 and Table 1.
[0089] Comparative Example 2
[0090] Take 38.2g of zirconium hydroxide powder and 18.0g of all-silicon MFI molecular sieve, mix them evenly, add 48.0g of 5% by mass sulfuric acid aqueous solution, soak at 40°C for 4h, and dry the soaked solid at 60°C for 12h and 120°C for 12h.
[0091] The dried solid was ground into fine powder, passed through a 100-300 mesh sieve, and peptized with a nitric acid aqueous solution having a concentration of 5.0 mass %, the mass ratio of the nitric acid aqueous solution to the fine powder being 0.6:1, and kneaded evenly to form a strip, and the wet strip was dried at 120° C. for 10 h and calcined at 680° C. for 4 h to obtain catalyst DA2. The composition and physicochemical properties of catalyst DA2 are shown in Table 1 and Table 1.
[0092] Comparative Example 3
[0093] The method of Example 2 was followed, except that an equal mass of white carbon black Si-2 (produced by Changling Catalyst Company, with a silicon oxide content of 99.9% by mass, XRD characterization see Figure 1 ) replaces the all-silicon MFI molecular sieve Si-1.
[0094] The prepared catalyst is recorded as catalyst DA3. The composition and physicochemical properties of catalyst DA3 are shown in Table 1 and Table 1.
[0095] Comparative Example 4
[0096] The method of Example 2 was followed, except that an equal mass of MCM-41 molecular sieve (denoted as Si-3, produced by Changling Catalyst Company, with a silicon oxide content of 99.7% by mass, XRD characterization see Figure 1 ) replaces the all-silica MFI molecular sieve.
[0097] The composition and physicochemical properties of the prepared catalyst, denoted as catalyst DA4, are shown in Table 1 and Supplementary Table 1.
[0098] Comparative Example 5
[0099] The method of Example 2 was followed, except that an equal mass of ZSM-5 molecular sieve (denoted as Si-4, produced by Changling Catalyst Company, with a silicon oxide / aluminum oxide molar ratio of 65, XRD characterization see Figure 1 ) replaces the all-silicon MFI molecular sieve Si-1.
[0100] The composition and physicochemical properties of the prepared catalyst, denoted as catalyst DA5, are shown in Table 1 and Supplementary Table 1.
[0101] Table 1
[0102]
[0103] Table 1
[0104]
[0105] Test Example 1
[0106] The following test examples are used to examine the isomerization reaction performance of the catalyst.
[0107] The activity of the catalysts prepared in the above examples and comparative examples was evaluated in a small fixed bed reactor using n-butane with a purity of >99.8 mass % as the reaction raw material. The evaluation conditions were: 245°C, 1.8 MPa, and a feed mass space velocity of 2.5 hr -1 , the hydrogen / hydrocarbon molar ratio was 1.0, and the evaluation results after reaction for 10 hours are listed in Table 2.
[0108] n-Butane conversion rate (%) = ((mass of n-butane in the feedstock - mass of n-butane in the product) / mass of n-butane in the feedstock) × 100%;
[0109] Isobutane selectivity (%) = (mass of isobutane in the product / (mass of normal butane in the feedstock - mass of normal butane in the product)) x 100%.
[0110] Table 2
[0111] Catalyst No. n-Butane conversion, mass % Isobutane selectivity, mass % A1 41.91 82.91 A2 40.96 84.04 A3 40.64 84.45 A4 39.98 83.41 A5 42.32 79.65 A6 38.98 82.00 DA1 40.45 77.81 DA2 28.67 80.00 DA3 34.89 79.63 DA4 34.46 80.44 DA5 40.89 71.30
[0112] Test Example 2
[0113] This test example is used to examine the normalization reaction performance of the catalyst.
[0114] The activity of the catalyst of the present invention and the comparative catalyst was evaluated in a small fixed bed reactor using isobutane with a purity of >99.8 mass % as the reaction raw material. The evaluation conditions were: 255°C, 1.8 MPa, and a feed mass space velocity of 2.5 hr -1 , the hydrogen / hydrocarbon molar ratio was 1.0, and the evaluation results after reaction for 10 hours are listed in Table 3.
[0115] Wherein, isobutane conversion rate (%) = ((mass of isobutane in the feedstock - mass of isobutane in the product) / mass of isobutane in the feedstock) × 100%;
[0116] Normal butane selectivity (%) = (mass of normal butane in the product / (mass of isobutane in the feedstock - mass of isobutane in the product)) x 100%.
[0117] Table 3
[0118]
[0119]
[0120] It can be seen from Table 2 and Table 3 that the catalyst provided by the present invention has a suitable density of strong acid centers compared with the comparative catalyst, and can take into account both excellent light alkane normal isomerization reaction activity and selectivity.
[0121] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for normal isomerization of alkanes, characterized in that: The catalyst includes an acidic active component SO4 2- / ZrO2, all-silicon molecular sieve with MFI structure and alumina; The mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.1-1).
2. The catalyst according to claim 1, wherein In the catalyst, the mass ratio of the acidic active component calculated as ZrO2 to the mass ratio of the all-silicon molecular sieve calculated as SiO2 is 1:(0.15-0.5).
3. The catalyst according to claim 1 or 2, wherein The catalyst comprises zirconium, silicon, aluminum and sulfur, respectively calculated as zirconium oxide, silicon oxide, aluminum oxide and SO3, based on the total mass of the catalyst, the content of zirconium oxide is 30-90wt%, the content of silicon oxide is 1-35wt%, the content of aluminum oxide is 5-50wt%, and the content of SO3 is 1-10wt%; preferably, based on the total mass of the catalyst, the content of zirconium oxide is 50-80wt%, the content of silicon oxide is 5-30wt%, the content of aluminum oxide is 5-30wt%, and the content of SO3 is 2-8wt%; Preferably, the mass ratio of SO3 to ZrO2 is (0.02-0.12):1, preferably (0.03-0.08):
1.
4. The catalyst according to any one of claims 1 to 3, wherein In the catalyst, the density of the strong acid center is 0.1-2 μmol / m 2 , preferably 0.5-1.5 μmol / m 2 ; Preferably, the specific surface area of the catalyst is 80-180m 2 / g; Preferably, the aluminum oxide is γ-Al2O3.
5. A method for preparing the alkane normal isomerization catalyst according to any one of claims 1 to 4, comprising: (1) mixing an all-silicon molecular sieve having an MFI structure and zirconium hydroxide to obtain a mixture; Wherein, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.1-1); (2) contacting the mixture with a solution containing sulfate; (3) The product obtained in step (2), an alumina precursor and an optional peptizing agent are mixed, and then molded and calcined.
6. The preparation method according to claim 5, wherein: The specific surface area of the all-silicon molecular sieve is 400-500m 2 / g; Preferably, the mass ratio of the zirconium hydroxide calculated by the mass of ZrO2 to the all-silicon molecular sieve calculated by the mass of SiO2 is 1:(0.15-0.5).
7. The preparation method according to claim 5 or 6, wherein: The contact temperature is 20-80°C, preferably 25-60°C; the contact time is 1-10h, preferably 2-5h; Preferably, the solution containing sulfate radicals is selected from an aqueous solution of at least one of sulfuric acid, ammonium sulfate and ammonium bisulfate; Preferably, the concentration of sulfate in the solution containing sulfate is 1-10wt%, preferably 2-8wt%; Preferably, the mass ratio of the solution containing sulfate to the mixture is 0.3-5:1, preferably 0.5-3:
1.
8. The preparation method according to any one of claims 5 to 7, wherein: The alumina precursor is pseudo-boehmite and / or gibbsite, preferably pseudo-boehmite; Preferably, the total mass ratio of the peptizing agent to the product obtained in step (2) to the alumina precursor is 0.3-1:1; Preferably, the peptizing agent is an aqueous solution of an acid, preferably an aqueous solution of at least one selected from nitric acid, acetic acid, citric acid, oxalic acid and formic acid.
9. The preparation method according to any one of claims 5 to 8, wherein: The molding method is selected from any one of extrusion molding, granulation molding, ball rolling molding and spray drying into balls, preferably extrusion molding; Preferably, in step (3), the calcination temperature is 600-850°C, preferably 650-850°C, and the calcination time is 1-20h, preferably 3-12h.
10. Use of the alkane normal isomerization catalyst according to any one of claims 1 to 4 in the normal isomerization reaction of light alkanes.
Citation Information
Patent Citations
Solid super acidic catalyst and preparation method thereof
CN101745407A
Preparation method of m-methoxyphenol
CN109503339A
Non-noble metal low-carbon alkane dehydrogenation catalyst, preparation method thereof and method for preparing low-carbon olefin through low-carbon alkane dehydrogenation
CN110614116A
Solid acid catalysis and separation integrated filler as well as preparation method and application thereof
CN114100644A
Process for preparing carried superstrong solid acid
CN1246386A